2016
DOI: 10.1155/2016/1093512
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Morphology and Estrogen Receptor-Alpha Expression in the Vagina of Ovariectomized Adult Virgin Rats by Estrogen Replacement: A Histological Study

Abstract: Background. To determine the exact role of estrogen in vaginal tissue morphology and estrogen receptor-alpha (ERα) distribution in the vagina, which remains controversial. Methods. Sixty rats were randomly categorized: sham-operated (sham), ovariectomy (OVX), and four estradiol treatments (estradiol valerate at 0.4, 0.8, 1.6, and 3.2 mg/kg/day) for 2 weeks. Thereafter, vaginal samples were biopsied from the distal- and proximal-half portions. The percentage of ERα-immunoreactive cells and the ERα score were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…ERα in the uterus plays an especially critical role in mediating estrogen action. Accordingly, a study showed that estrogen deficiency induced atrophy in the uterus of OVX rats [32]. In the present study, the CO + RF extract increased the mRNA expression of mouse ERα (ESR1) in the murine uterus and estradiol secretion in ADD-induced COV434 granulosa cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…ERα in the uterus plays an especially critical role in mediating estrogen action. Accordingly, a study showed that estrogen deficiency induced atrophy in the uterus of OVX rats [32]. In the present study, the CO + RF extract increased the mRNA expression of mouse ERα (ESR1) in the murine uterus and estradiol secretion in ADD-induced COV434 granulosa cells.…”
Section: Discussionsupporting
confidence: 57%
“…Since uterine weight and morphology is regulated by estrogen concentrations [32], we investigated the effects of CO + RF mixtures of uterine weight in the OVX mice model. OVX mice resulted in reduced uterine weight and uterine atrophy, compared to the sham group.…”
Section: Estrogenic Effects Of Co + Rf On Uterus In Ovx Mice and On Cov434 Granulosa Cellsmentioning
confidence: 99%
“…Eight weeks after OVX, VBF ceased to be affected by PTNS, however. The OVX surgery causes vaginal atrophy [23] and decreases vaginal innervation [24] in both rats and humans [25]. Over time, this could decrease the target organ’s ability to be stimulated or provide an adequate response to PTNS.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone enanthate dosage at 50 mg/kg BW (Bayer Pharma AG, BER, Germany) was derived from our pilot study. Estradiol valerate dosage at 1.6 mg/kg BW was derived from Li T and colleagues [ 19 ], having been proven to be effective in reducing obesity and vulvovaginal atrophy in ovariectomized rats. Additionally, genistein dosage at 16 mg/kg BW was based on our previous publications, which demonstrated its efficacy in improving NASH induced via OVX + HFHF diet in female rats [ 14 , 20 ].…”
Section: Methodsmentioning
confidence: 99%